2006
DOI: 10.1007/s10681-006-9281-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis as influenced by male-sterility inducing cytoplasms in sorghum [Sorghum bicolor (L.) Moench]

Abstract: An investigation was carried out to assess the efficiency of A 2 cytoplasmic-nuclear male-sterility (CMS) system in comparison to the widely used A 1 cytoplasm in terms of general combining ability (gca) effects of male-sterile (A-) lines and mean performance, specific combining ability (sca) effects and mid-parent heterosis of hybrids for days to 50% flowering, plant height and grain yield at International Crops Research Institute for the Semi-Arid Tropics, Patancheru, Andhra Pradesh, India in 2001 and 2002 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…Since these male sterile lines were recently introduced into Africa from different climatic conditions, some could be poorly suited for the new agroecologies. The temperature at the three locations ranged between 18 and 29.3°C which is within the optimum range for most sorghum cultivars (Reddy et al, 2007).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Since these male sterile lines were recently introduced into Africa from different climatic conditions, some could be poorly suited for the new agroecologies. The temperature at the three locations ranged between 18 and 29.3°C which is within the optimum range for most sorghum cultivars (Reddy et al, 2007).…”
Section: Resultsmentioning
confidence: 82%
“…The best cross combinations that showed significant and positive SCA effects for productive tillers per plant were ATX623×Macia, ICSA88001×ICSR 93034 and ICSA90001×ICSR162. Productive tillers in sorghum parents are desirable as they provide pollen for longer time as compared to non-tillering ones and do add to grain yield of a particular parent as supported by Reddy et al (2007) and Singh et al (1997). Considering the plant height, the best crosses that expressed significant negative (desired) SCA effect comprised of ICSA376×IESV23O13DL (-43.90), ICSA6×ICSR93034 (-43.25), ICSA276 × IESV91104DL (-31.26), MA6×S35 (-28.35) and MA6×Makueni local (-23.73).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…ICRISAT has also developed a number of varieties targeting the semi-arid tropics of Africa and Asia (Kumar et al, 2011). Inbred parental lines have been developed for hybrid breeding targeting Asia, which have also been started to be used by breeding programs Africa (Kumar et al, 2011, Reddy et al, 2007.…”
Section: Sorghum Breeding In the Worldmentioning
confidence: 99%
“…The A1 and A2 CMS systems can be used for seed production to produce commercially acceptable F1 hybrids. In addition, studies have shown that the two systems had no significant difference in agronomic performances (Moran and Rooney, 2003;Reddy et al, 2007). However, the A1 CMS system, which was derived from backcrossing the kafir sorghum type that have recessive fertility restoration nuclear genes in the background of a Milo cytoplasm, has been exclusively used in sorghum hybrid development for more than five decades.…”
Section: Sorghum Hybridsmentioning
confidence: 99%